Survei Kondisi Fisik Futsal Dominan Pemain Futsal Vasco Academy Lamongan Usia 18-20 Tahun - Insan Muhtadawan Ramadhan; Supriatna Supriatna; Yulingga Nanda Hanief (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Physical condition is a basic need for every sports athlete to support the performance of the players in carrying out activities to reach their achievements. The purpose of this study is to determine the physical abilities of futsal athletes at vasco Academy Lamongan. The method used is a survey with a test and measurement techniques. Samples were taken from 15 vasco academy lamongan futsal players. The components include speed, agility, power and aerobic endurance. The result of physical conditioning with very good categories, were speed and power medium category was agility and in less category was aerobic endurance. With an average value of 4.5 speed, agility 19.77, power 232 and endurance 39.46. The conclusion from the study is that the physical condition of futsal players at vasco academy Lamongan is in the good category, with the percentage shown at 81% according to the prevailing norms.